Childhood and linguistic displacement: reflections on the role of speech in the socialization of Toba children in Buenos Aires - Hecht, Ana Carolina (2009)
This paper will analyze the relationship between language practices and childhood among Toba children. The study focused on a marginal urban setting in Buenos Aires where monolingual practices are replacing bilingual ones. Consequently, many children are rapidly shifting to Spanish and loosing their command of the Toba language. Through an ethnographic research, we observed native childhood categorization (nogotshaxac) to systematize the meanings, implicit and explicit, that languages have along different moments in children’s life.